2023
DOI: 10.3390/ijms24076821
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Linkage Glucan Is the Main Carbohydrate Source and Starch Is an Alternative Source during Brachypodium Grain Germination

Abstract: Seeds of the model grass Brachypodium distachyon are unusual because they contain very little starch and high levels of mixed-linkage glucan (MLG) accumulated in thick cell walls. It was suggested that MLG might supplement starch as a storage carbohydrate and may be mobilised during germination. In this work, we observed massive degradation of MLG during germination in both endosperm and nucellar epidermis. The enzymes responsible for the MLG degradation were identified in germinated grains and characterized u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…MLGs have been implicated in resistance of barley cultivars to infection by the cereal cyst nematode (Aditya et al, 2015). MLGs in the grasses are also used for both long-term and short-term secondary sources of metabolizable glucose, where their synthesis and depolymerization are more direct, simpler and potentially faster in comparison to starch (Francin-Allami et al, 2023;Roulin et al, 2002;Trafford et al, 2013). Whether these factors contribute to any competitive advantage in the grasses remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…MLGs have been implicated in resistance of barley cultivars to infection by the cereal cyst nematode (Aditya et al, 2015). MLGs in the grasses are also used for both long-term and short-term secondary sources of metabolizable glucose, where their synthesis and depolymerization are more direct, simpler and potentially faster in comparison to starch (Francin-Allami et al, 2023;Roulin et al, 2002;Trafford et al, 2013). Whether these factors contribute to any competitive advantage in the grasses remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…MLG is also found as a reserve polysaccharide in the seeds of cereal grains ( Morrall and Briggs 1978 ). Use of MLG as a reserve polysaccharide has been studied in detail in the model grass Brachypodium distachyon , where it is present in thick endosperm cell walls and is mobilized during seedling germination ( Francin-Allami et al 2023 ). Although xylans are also found in seeds of some plants, the arabinoxylan from the seed husks of Plantago ovata has received the most attention ( Belorio and Gomez 2022 ).…”
Section: The 5 Major Polymers Of the Plant Cell Wallmentioning
confidence: 99%
“…β-glucan content varies between genus, within species, between varieties, and in relation to developmental stage and growing environment [ 98 , 99 , 100 , 101 ]. It is suggested that β-glucans are not essential structural components of cells walls but rather represent a secondary source of metabolizable energy in the form of glucose [ 102 , 103 , 104 ]. Any attempt at adjusting the amount of β-glucan could therefore have a knock-on effect on the carbon pool in the plant.…”
Section: Mixed Linkage β-Glucanmentioning
confidence: 99%